Kelangsungan Hidup Larva Ikan Nila yang Berasal Dari Induk yang Diberi Pakan Berimunostimulan - Maleko, Ayu; Sinjal, Hengky J; Manoppo, Henky (Universitas Sam Ratulangi, 2014)
The objective of this research was to evaluate the effect of feed supplemented with baker’s yeast on survival rate of nile tilapia larvae and to determine the effective dose of baker’s yeast that could optimally improve larval quality. The research was conducted at Pathology and Clinic of Fish Disease from June – September 2014. Fish as brood stock candidates was cultivated at five concrete tanks (2x1x1 m3) at a density of 30 fish per tank. Each tank was equipped with water inlet, outlet and water pump for recirculating and aerating. After seven days of adaptation, fish was fed pellet supplemented with baker’s yeast at five different doses (0, 10, 20, 30, 40 g/kg food) for four consecutive weeks at 4%/bb/day, twice daily. Larva was captured with seser and moved into five glass aquaria with density of 20 larvae/aquarium and reared for two weeks. Data collected was survival rate of larvae achieved until the end of larval rearing. Research result showed that larvae produced by brood stock fed food supplemented with 10 g baker’s yeast per kg food had the highest survival rate namely 60%. As conclusion, supplementation of baker’s yeast into brood stock feed might increase survival rate of larvae. Keywords: nile tilapia, baker’s yeast, larvae, survival rate